2002
DOI: 10.1002/sia.1360
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of NH3 with oxygen‐pretreated Ni at 600 K

Abstract: The aim of the present study was to investigate the reaction between ammonia and pre-adsorbed oxygen on Ni at 600 K using metastable impact electron spectroscopy (MIES) and UPS techniques. For a given oxygen-pretreated nickel surface, the changes in the MIES spectra along with ammonia adsorption can be decomposed into three different steps: a first domain without significant changes, a second domain corresponding to drastic changes in the intensity of a signal at 15.8 eV; and a third domain where no more chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The subtraction of the latter spectrum from the NiO spectrum highlights three weak peaks at 6.8, 9.4, and 12.3 eV BE, respectively. These structures have already been observed at high temperature and attributed to NH x ( x = 1, 2) compounds . Let us note that, at 600 K, the superposition of poorly intense structures leads to a structureless and slight plateau …”
Section: Resultsmentioning
confidence: 68%
See 4 more Smart Citations
“…The subtraction of the latter spectrum from the NiO spectrum highlights three weak peaks at 6.8, 9.4, and 12.3 eV BE, respectively. These structures have already been observed at high temperature and attributed to NH x ( x = 1, 2) compounds . Let us note that, at 600 K, the superposition of poorly intense structures leads to a structureless and slight plateau …”
Section: Resultsmentioning
confidence: 68%
“…Over a recent study about NH 3 exposure on oxygen-pretreated polycrystalline Ni at high temperature (600 K), we observed that surface-adsorbed oxygen atoms react with ammonia, and that, finally, water is desorbed while atomic nitrogen partly covers the surface. However, because of the high temperature, neither the intermediate adspecies nor the phases containing oxygen on the surface O-adsorbed and/or NiO islands were identified.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations